PSYCHOSOCIAL CHARACTERISTICS OF BULLYING PERSONALITY - Bošković, Milo (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Violence as a traditional appearance of a criminal nature in modern conditions is expressed in certain specific circumstances, especially the type and application of funds. However, behind the phenomena are violent - offender and victim. Criminology, even in its infancy of science, as well as in the classical theories have always dealt with the issues of violent offender, classifying it in the first criminals of passion. The question is whether modern conditions with changes in the type and nature of violence in recent times this type of crime and became a rational motive, and therefore habitually delinquent or professional criminal. The work in this regard primarily engaged in matters of general (psychological, pathological and social) characteristics and dispositions of perpetrators of violence in the area.